MODEL SIMULASI DAN RANCANG BANGUN KAPASITAS USAHA PENYULINGAN MINYAK NILAM - Agus Supriatna Somantri dan Djajeng Sumangat (Jurnal Teknologi Industri Pertanian, 2007)
ABSTRACTEssential oil product as an export commodity has always been possessed an increasing world market in spite of facing hard competition and non-tariff barrier in the world trade; therefore there is a need to formulate a policy and an effort to increase the productivity and efficiency of integrated and sustainable essential-oil agroindustry.  This research aimed at providing the database of essential oil distillation system especially for the patchoully oil at variouse economic scale.  This database can be used as an input for engineering design system as well as for patchoully oil agroindustry system.  The methods used were analytical, numerical and econometrical which were supported by empirical and theoretical data. The research results showed that mathematical model constructed for prediction and optimization of essential oil distillation especially for patchoully-oil had the capability to generate integrative information of predictive equipments dimensions, rate of distillation and energy consumption.  Based on the mathematical model, theoretical pathcoully oil distillation time was 8 hours in order to produce average yield 2.54 %.  The quantity of the patchoully oil for each distillation process had positive correlation with the distillation capacity.  Economical analysis on essential oil distillation at variouse economic scale showed that the cost of distillation equipment at development level had positive correlation with the distillation capacity.  The minimum price of patchoully oil which was still profitable followed the equation y = 3 x 106x-0.4693 (R2 = 0.9891) if kerosene used as energy source. Keywords: Simulation, distillation, essential oil, patchoully.